Application of the Discovery Learning Learning Model to Increase Student Activity and Learning Outcomes in the Subject of Fundamentals of Plant Cultivation at Vocational High Schools in Takalar Regency - Santi Nursuci; Husain Syam; Jamaluddin P (Formosa Journal of Applied Sciences, 2023)
This research is a classroom action research to increase the activity and learning outcomes of students in class X ATP SMKN 6 Takalar. In this study, the independent variable is the application of the discovery learning model, while the dependent variable is the activeness and student learning outcomes in the basics of plant cultivation. The population of this study were all SMKs in Takalar district which had the basics of plant cultivation as a subject, while the sample was class X ATP SMKN 6 Takalar. The research data were obtained by observing student activities using activity observation sheets, and learning outcomes tests were in the form of pre-test and post-test. Based on data analysis, it was concluded that by applying the discovery learning learning model it could increase the activity and learning outcomes of class X ATP SMKN 6 Takalar.